Ecosystems and Human Health: Toxicology and Environmental Hazards, Second Edition - Philp, Richard B. (CRC Press, 2009)
Renamed to reflect the expanded scope of the second edition, Ecosystems and Human Health: Toxicology and Environmental Hazards builds on the foundation created by the author in the first edition, Environmental Hazards and Human Health. Written in a journalistic, easily accessible style, this book bridges the gap between toxicology and environmental sciences by exploring man-made and natural hazards, and the risks they pose to wildlife and human health. See what's new in the Second Edition: